Accuracy of Interpolated Versus In-Vineyard Sensor Climate Data for Heat Accumulation Modelling of Phenology - Pipan, Paula; Hall, Andrew; Rogiers, Suzy Y.; Holzapfel, Bruno P. (Frontiers in Plant Science, 2021)
Background and aims: In response to climate change, accurate climate data are required to calculate climatic indices for long-term decisions about vineyard management, vineyard site selection, varieties planted and to predict phenological development. Availability of spatially interpolated climate data has the potential to make viticultural climate analyses possible at specific sites without the expense and uncertainty of collecting climate data within vineyards. The aim of this study was to compare the accuracy and precision of climatic indices calculated using on-site climate sensor and interpolated climate datasets to assess whether the effect of spatial variability in climate at this fine spatial scale significantly affects phenological modelling outcomes. Methods and results: Four sites comprising two topographically homogenous vineyards and two topographically diverse vineyards in three wine regions in Victoria (Australia) were studied across four growing seasons. A freely available database of interpolated Australian climate data based on government climate station records (Scientific Information for Land Owners, SILO) provided temperature data for grid cells containing the sites (resolution 0.05° latitude by 0.05° longitude, approximately 5 km × 5 km). In-vineyard data loggers collected temperature data for the same time period. Results indicated the only significant difference between the two climate data sources was the minimum temperatures in the topographically varied vineyards where night-time thermal layering is likely to occur. Conclusion: Interpolated climate data closely matched in-vineyard recorded maximum temperatures in all cases and minimum temperatures for the topographically homogeneous vineyards. However, minimum temperatures were not as accurately predicted by the interpolated data for topographically complex sites. Therefore, this specific interpolated dataset was a reasonable substitute for in-vineyard collected data for vineyard sites that are unlikely to experience night-time thermal layering. Significance of study: Access to accurate climate data from a free interpolation service, such as SILO provides a valuable tool to manage blocks or sections within vineyards more precisely for vineyards that do not have a weather station on site. Care, nevertheless is required to account for minimum temperature discrepancies in topographically varied vineyards, due to the potential for cool air pooling at night, that may not be reflected in interpolated climate data.